Insulin therapy adherence and its associated factors among diabetic patients in a Ghanaian primary care hospital. - Israel Abebrese Sefah; Michael Mensah; Araba Ata Hutton-Nyameaye; Emmanuel Sarkodie; Johanna C Meyer; Brian Godman; Varsha Bangalee (PLoS ONE)
Background Diabetes mellitus (DM) is a global health problem. Adherence to intensive insulin therapy is necessary to achieve better glycemic control in types 1 and 2 DM. This study aimed to evaluate the extent of adherence to insulin therapy, its predictors and to identify barriers to its adherence. Method This was a cross-sectional survey among adult (≥18 years) diabetic patients who are currently using insulin, either alone or in combination with an oral antidiabetic regimen, and seeking primary care at Kwame Nkrumah University of Science and Technology Hospital in Ghana. A total of one hundred and eight-six patients were conveniently sampled, and interviewed. Insulin adherence was determined using the Medication Adherence Reporting Scale-5. Descriptive statistics, a chi-square test of independence, and a multiple logistic regression analysis were performed using STATA version 14 (StataCorp, TX USA). Results The majority of the patients interviewed were over 60 years (40.32%); female (61.83%); married (68.82%); and had completed secondary education (48.39%). 67.20% of the patients were adherent to insulin therapy. Adherence level was associated with age (p = 0.020), marital status (p = 0.001), employment status (p = 0.012), type of DM (p<0.001), regular follow-up (p = 0.007) and comorbidities (p = 0.002) and was only predicted by the type of DM (aOR = 14.82 C.I 1.34-163.50, p-value = 0.028). Conclusion Adherence to insulin therapy among our study population was suboptimal, which is a concern considering the associated increased risk of complications. Adherence assessment and counselling by healthcare professionals to address barriers to poor adherence must be continually undertaken to achieve optimal glycemic control. Impact of findings on practice statements Continuous adherence assessment and counselling must be offered to all diabetes mellitus patients on insulin therapy as part of their ambulatory care to help improve outcomes.Using the Medication Adherence Reporting Scale-5 to determine patient adherence levels is an easy-to-use and an inexpensive method; however, it should be used with caution due to the potential for misclassification.Efforts must be made to provide appropriate strategies to deal with barriers to insulin adherence at ambulatory care clinics as part of the individualized comprehensive diabetic care to reduce diabetic complications.